2016
DOI: 10.3390/cells5020016
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Pathway and Cancer Stem Cells

Abstract: The NF-κB transcription factor pathway is a crucial regulator of inflammation and immune responses. Additionally, aberrant NF-κB signaling has been identified in many types of cancer. Downstream of key oncogenic pathways, such as RAS, BCR-ABL, and Her2, NF-κB regulates transcription of target genes that promote cell survival and proliferation, inhibit apoptosis, and mediate invasion and metastasis. The cancer stem cell model posits that a subset of tumor cells (cancer stem cells) drive tumor initiation, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(190 citation statements)
references
References 179 publications
10
173
0
7
Order By: Relevance
“…NF-kB, a transcription factor that displays vital roles in inflammation, immunity, cell proliferation, differentiation, and survival, has been proved to be a major signaling pathway in the development of various inflammation-related diseases, which is mediated by TLR4 to perform regulation of inflammation. [49][50][51][52] NF-kB has been treated as a central link in the pathogenic processes of systemic inflammatory response and kidney injury to high fat exposure. 53,54 As expected, in the present study, on one hand, HFD-fed mice were found to have a significant upregulation in TLR4/NF-kB activation, resulting in the expression of proinflammatory cytokines and related chemokines, including IL-β, IL-6, TNF-α, MCP-1, Cxcr4, Emr-1, and MIP-1α.…”
mentioning
confidence: 99%
“…NF-kB, a transcription factor that displays vital roles in inflammation, immunity, cell proliferation, differentiation, and survival, has been proved to be a major signaling pathway in the development of various inflammation-related diseases, which is mediated by TLR4 to perform regulation of inflammation. [49][50][51][52] NF-kB has been treated as a central link in the pathogenic processes of systemic inflammatory response and kidney injury to high fat exposure. 53,54 As expected, in the present study, on one hand, HFD-fed mice were found to have a significant upregulation in TLR4/NF-kB activation, resulting in the expression of proinflammatory cytokines and related chemokines, including IL-β, IL-6, TNF-α, MCP-1, Cxcr4, Emr-1, and MIP-1α.…”
mentioning
confidence: 99%
“…The NF-κB signaling pathway has also been linked with several cancers by regulating transcription of its downstream target genes, including genes involved in cell cycle pathway [28, 40]. Many studies have found that NF-κB signaling was exceedingly activated and some target genes of NF-κB were upregulated in several cancers [4143].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying molecular mechanisms might be attributed to its regulation on the RKIP -NF-κB-Snail circuit, which had been demonstrated in this study. Especially, as one of the most investigated transcription factors, NF-κB has been proved to regulate multiple cellular processes in cancer, including proliferation, invasion, metastasis, angiogenesis, and chemoresistance [14, 15]. …”
Section: Discussionmentioning
confidence: 99%